Management of Chronic Expanding Haematoma Using Triamcinolone after Latissimus Dorsi Flap Harvesting - Hamada, Mariko; Shimizu, Yusuke; Aramaki-Hattori, Noriko; Kato, Tatsuya; Takada, Keiko; Aoki, Marie; Kishi, Kazuo; Nagasao, Tomohisa (Archives of Plastic Surgery, 2015)
Chronic expanding haematoma (CEH) is a rare type of haematoma that enlarges slowly and continuously without coagulation. It can occur following surgery because of shear stress-induced bleeding in the scar tissue between the subcutaneous fat and fascia. We present three cases of large chronic CEH that were successfully treated with triamcinolone injections. Three female patients developed large chronic CEH at 9 months, 5 years, and 6 years, respectively, after latissimus dorsi flap harvesting for breast reconstruction. Although the condition did not improve after multiple sessions of haematoma aspiration in the first two patients, it resolved following a single 40-mg triamcinolone injection along with appropriate compression dressing for several weeks. In the third patient, triamcinolone was injected immediately after the initial aspiration of the haematoma, and the condition improved considerably. There were no side effects in any of the patients. To the best of our knowledge, this is the first report of successful treatment of large CEH using triamcinolone. Therefore, we suggest that triamcinolone injections be considered for the treatment of CEH.
Keywords: Haematoma; Triamcinolone; Free tissue flaps; Seroma